Assessing the Possibility of Medupi and Kusile Providing Enough Electricity Running at Full Capacity in South Africa - Hlongwane, Nyiko Worship; Daw, Olebogeng David (International Journal of Energy Economics and Policy, 2023)
This study assesses the possibility of Kusile and Medupi power plants with providing enough electricity to the South African economy when generating at full capacity. The study utilised time series data spanning from 1980 to 2021 collected from secondary sources such as the International Energy Agency and the World Bank. The study employed DF-GLS and PP unit root tests, ARDL Bounds test, ARDL ECM model and Granger causality tests to assess the possibility. The results revealed that there is a positive relationship between electricity generation, economic growth, and population growth on electricity consumption while electricity loss and trade openness were negatively related to electricity consumption. The granger causality results revealed unidirectional causality running from electricity consumption to economic growth and from trade openness to electricity consumption. The study recommended that Eskom and South African government should speed up the completion of Medupi and Kusile power plants, limit electricity loss and investing in new electricity infrastructure to match the gap between demand and supply and limit loadshedding in South Africa.